Soft Sensing Image Analysis and Processing Method of Substation Equipment Defects - Banihashemi, Saeed; Zhang, Jingxiao (International Journal for Applied Information Management, 2023)
In the context of incentivizing regulation for distribution companies, the utilization of a reference network model proves to be a valuable tool for evaluating their effective cost. These models play a crucial role in planning expansive distribution areas that encompass various voltage levels. This paper introduces a green space planning algorithm designed to optimize the location, size, and power supply areas of medium and low voltage substations within the Reference Network Model (RNM). The algorithm aims to enhance the efficiency and environmental impact of these substations. The focus of this study extends to two key aspects: the creation of "environment-friendly" substations and the significance of implementing "resource-saving" substations in China. The evaluation of "environment-friendly" and "resource-saving" characteristics is conducted through comprehensive analysis, with results indicating notable features. Feature 1, associated with environmental friendliness, is measured at 0.363, while Feature 2, emphasizing resource-saving attributes, achieves a high score of 0.835. Furthermore, Feature 3, addressing the importance of implementing these eco-friendly substations in the Chinese context, attains a commendable score of 0.824. The findings underscore the potential of the proposed green space planning algorithm in enhancing the sustainability and efficiency of medium and low voltage substations within the incentive regulation framework for distribution companies.